2016
DOI: 10.1007/s11998-016-9842-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface-initiated growth of copper using isonicotinic acid-functionalized aluminum oxide surfaces

Abstract: Isonicotinate self-assembled monolayers (SAM) were prepared on alumina surfaces (A) using isonicotinic acid (iNA). These functionalized layers (iNA-A) were used for the seeded growth of copper films (Cu-iNA-A) by hydrazine hydrate-initiated electroless deposition. The films were characterized by scanning electron microscopy (SEM), electron-dispersive X-ray spectroscopy, atomic force microscopy, Xray photoelectron spectroscopy, X-ray diffraction, and advancing contact angle measurements. The films are Cu 0 but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 40 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…[20][21][22] We have also shown that functionalization with pyridine, phosphines, and thiols of CNTs can be achieved in a number of ways and this allows for coordination of metal ions, compounds or 4 nanoparticles. [23][24][25][26][27] Of these substituents, pyridine functionality not only acts as an efficient ligand, 24,28,29 but also facilitates a decrease in the copper reduction potential, resulting in the preferential reduction of the surface bound Cu(II) to Cu(I). [29][30][31][32][33][34][35] This coordinated Cu can then act as a catalyst for the deposition of further Cu(II) ions from solution, allowing controlled seeded growth by electroless deposition.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22] We have also shown that functionalization with pyridine, phosphines, and thiols of CNTs can be achieved in a number of ways and this allows for coordination of metal ions, compounds or 4 nanoparticles. [23][24][25][26][27] Of these substituents, pyridine functionality not only acts as an efficient ligand, 24,28,29 but also facilitates a decrease in the copper reduction potential, resulting in the preferential reduction of the surface bound Cu(II) to Cu(I). [29][30][31][32][33][34][35] This coordinated Cu can then act as a catalyst for the deposition of further Cu(II) ions from solution, allowing controlled seeded growth by electroless deposition.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35] This coordinated Cu can then act as a catalyst for the deposition of further Cu(II) ions from solution, allowing controlled seeded growth by electroless deposition. 28,29,36 In the case of CNTs, we have reported that pyridine (py) functionalization may be achieved through 1,3-dicyclohexylcarbodiimide (DCC) coupling of isonicotinic acid (with CNT-OH groups) or 4-hydroxypyridine (with CNT-CO 2 H groups). 24 Based upon the forgoing, we proposed a study to understand and control the seeded growth of Cu on functionalized CNTs in order to synthesize templates for subsequent Cu growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arai et al prepared Cu-MWCNT and Cu-SWCNT composites using glyoxylic acid as a reducing agent; however, surfactants and high-energy disaggregation methods (e.g., mechanical atomization) were necessary to obtain well-dispersed CNTs in copper matrix [12][13][14]. Using a different approach, our group has successfully transferred expertise in electroless deposition of copper from alumina to CNT surfaces [15,16]. Covalent functionalization with nitrogen bearing molecules, such as isonicotinic acid and pyridine on the surface of alumina and SWCNTs, respectively, allowed an even distribution of copper particles thanks to seeding effect of nitrogen functionalities [16].…”
Section: Introductionmentioning
confidence: 99%
“…Using a different approach, our group has successfully transferred expertise in electroless deposition of copper from alumina to CNT surfaces [15,16]. Covalent functionalization with nitrogen bearing molecules, such as isonicotinic acid and pyridine on the surface of alumina and SWCNTs, respectively, allowed an even distribution of copper particles thanks to seeding effect of nitrogen functionalities [16]. On the other hand, CNT functionalization can also affect electrodeposition; for this reason, we have performed this study to closely examine the effect of CNT functionalization during electrodeposition of copper.…”
Section: Introductionmentioning
confidence: 99%